PENGARUH KESADARAN DIRI TERHADAP HASIL BELAJAR SISWA - Syahid Alviansyah; Muhammad Fauzi; Baldi Anggara (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2022)
This research was conducted in MTs paradigm Palembang with the aim of finding out whether or not there is an influence of self-confidence on students' learning outcomes in aqidah ahlaq class XI MTs paradigm Palembang Academic Year 2020/2021. The procedure of conducting the survey.This type of research is quantitative research with data collection techniques using questionnaires, documentation and literature. The data analysis technique used normality test, heteroscedasticity test and linearity test, and simple regression analysis consisting of the coefficient of determination test and t-test (partial).The results of the research Based on the results of calculations using the SPSS 21.0 program as shown in the table above, the results of the research in this study, obtained the value of t arithmetic > t table (2.064> 2.04841) and the results of a significance of 0.048 <0.05 self-awareness has an important impact on student learning outcomes. Students who have awareness of their learning outcomes can learn diligently and listen to the teacher explaining the lesson. There is an influence between self-concept and students' learning outcomes, students who have awareness of their learning outcomes can study seriously, there is enthusiasm and motivation for achievement, and with a strong self-confidence, students no longer fall asleep, do not listen to what is given by the teacher